The redesigned Forensic Research/Reference on Genetics-knowledge base, FROG-kb. (March 2018) - Kidd, Kenneth K.; Soundararajan, Usha; Rajeevan, Haseena; Pakstis, Andrew J.; Moore, Katherine N.; Ropero-Miller, Jeri D.
Abstract: The Forensic Resource/Reference on Genetics-knowledge base (FROG-kb) web site <https://frog.med.yale.edu/FrogKB/> was introduced in 2011 and in the five years since the previous publication ongoing research into how the database can better serve forensics has resulted in extensive redesign of the database interface and functionality. Originally designed as a prototype to support forensic use of single nucleotide polymorphisms (SNPs), FROG-kb provides a freely accessible web interface that facilitates forensic practice and can be useful for teaching and research. Based on knowledge gained through its use, the web interface has been redesigned for easier navigation through the multiple components. The site also has functional enhancements, extensive new documentation, and new reference panels of SNPs with new curated data. FROG-kb focuses on single nucleotide polymorphisms (SNPs) and provides reference population data for several published panels of individual identification SNPs (IISNPs) and several published panels of ancestry inference SNPs (AISNPs). For each of the various marker panels with reference population data, FROG-kb calculates random match probabilities (RMP) and relative likelihoods of ancestry for a user-entered genotype profile (either completely or partially specified). Example genotype profiles are available and the User's Manual presents interpretation guidelines for the calculations. The extensive documentation along with ongoing updates makes FROG-kb a comprehensive tool in facilitating use of SNPs in forensic practice and education. An overview of the new FROG-kb with examples and material explaining the results of its use are presented here.